Boundary Control Design for a Flexible Manipulator with Input Backlash *. Issue 1 (July 2017) - Zou, Mingfo; He, Wei; He, Xiuyu; Zhao, Minghao; Yang, Chuan; Li, Guang
Abstract: Boundary control design for a class of flexible manipulator with input backlash is our uppermost work of this paper. The original infinite dimensional model of the manipulator is represented by a partial differential equation (PDE) and a set of ordinary differential equations (ODEs). Our control aims are: 1) moving the manipulator to the certain desired angle; 2) suppressing the vibration at the neighbourhood of the desired angle; 3) handling the backlash nonlinearity existing in the practical system. The stability of the system and the effectiveness of the designed controller are analysed by Lyapunov's direct method and numerical simulation.